PROCESS OF POSSIBLE CURE OF YELLOW FEVER INFECTION THROUGH LYOPHILIZATION OF THE LIQUID DRUG OF THE MITIGATIONAL VIRUS AND ITS ADMINISTRATION IN THE FOREST THROUGH SPRAYING - Vilela de Faria Nunes, Wanessa (Journal of Interdisciplinary Debates, 2021)
The research opted for the general purpose of formulating the drug on a large scale and its dissemination after lyophilization by spraying. And for the following specific objectives: to apply the methodology in a specific laboratory; evaluate the level of cure by spraying the mosquito on a large scale; determine the possible cure through research. The mosquito Aedes aegypti is the main transmitter of the yellow fever virus in cities, this virus is also present in forests, the virus in turn contaminates the mosquito which in turn stings the monkey, which then begins to suffer from the disease. Then the problem arises: a virus-free insect that sucks the blood of this contaminated primate starts charging the yellow fever cause. And then you can pass it on to another monkey, which can spread it to another mosquito, in the forest regions, the insects of the genera Haemagogus or Sabethes bite monkeys with the disease and then pass it on to humans in the vicinity. It is plausible that Aedes Aegypti disseminates yellow fever in the cities, it is a vicious circle that has occurred for many, many years in the Brazilian forests. Mosquitoes of the genera Haemagogus and Sabethes only circulate through areas of forest. Now, if a person visits a forest or lives near another, for example, they may be bitten by one of those infected mosquitoes. And there, you run the risk of having wild yellow fever.